Draft Ninth Five Year Plan (1997-2002) and Annual Plan 1997-98 (Volume III) National Capital Territory of Delhi - Planning Commission (Planning Commission, 1997)
Progress of expenditure and physical achievements during Eight five year plan outlay for Ninth five year Plan (1997-2002) and Annual Plan 1997-98, Agriculture and Allied Services, Co-operation, Rural Development, Minor Irrigation, Flood Control, Energy, Industry and Minerals, Weight and Measure.
Planning Department, Govt. of NCT of Delhi